Strategie rozvoje rodinného podniku - Springer, Pavel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Tato diplomová práce se zabývá návrhem strategie rozvoje rodinného podniku Vinařství SPRINGER a.s. V první části práce jsou vymezeny teoretické pojmy týkající se dané problematiky. Druhá část je věnována analýze současného stavu vybraného rodinného podniku a v poslední části této práce je na základě provedené analýzy zpracován návrh strategie rozvoje tohoto rodinného podniku.

This master thesis deals with a proposal of development strategy of family business Vinařství SPRINGER a.s. The first part of the thesis defines theoretical concepts of the topic. The second part is devoted to an analysis of the current state of the chosen family business and in the last part of this thesis, based on the analysis, is created a proposal of development strategy of this family business.
Development Strategy of Family Business
Keywords: Rodinný podnik; strategie; rozvoj; strategická analýza; SWOT analýza; návrh strategie rozvoje; Family business; strategy; development; strategy analysis; SWOT analysis; proposal of development strategy